Impact of Adjuvant Therapy on Survival in Surgically Resected Limited-Stage Small Cell Lung Cancer - Li, Di; Deng, Chaoqiang; Zheng, Qiang; Fu, Fangqiu; Wang, Shengping; Li, Yuan; Chen, Haiquan; Zhang, Yang (Frontiers in Oncology, 2021)
Background: Data on efficacy of adjuvant therapy for surgically resected small cell lung cancer are scant. This study was determined to reveal the survival benefits of different adjuvant treatment modalities for limited-stage small cell lung cancer patients following surgical resection. Methods: Data of patients with histologically confirmed small cell lung cancer after surgical resection were collected from November 2006 to June 2019. Survival analyses were calculated by Kaplan–Meier method, with log-rank test to evaluate statistical significance. Prognostic factors were identified by multivariate analysis using cox proportional hazards model. Further survival analysis and cox regression analysis stratified by clinicopathologic features were conducted to evaluate the survival benefits of different adjuvant treatment modalities. Results: In total, 153 out of 157 patients were analyzed. Multivariate analysis showed male sex, lymph node metastasis, residual tumor, VPI and non-adjuvant therapy were independently associated with poor prognosis. Subgroup analyses revealed both adjuvant chemotherapy and adjuvant chemoradiotherapy were significantly associated with superior survival for stage pT2-4 (HR=0.176, 95%CI:0.053-0.578, p=0.004; and HR=0.115, 95%CI:0.033-0.405, p=0.001) and pure SCLC patients (HR=0.182, 95%CI:0.067-0.494, p=0.001; and HR=0.181, 95%CI:0.071-0.465, p<0.001). For pN0 patients, adjuvant chemotherapy was associated with better survival (HR=0.219, 95%CI:0.054-0.891, p=0.034), while adjuvant chemoradiotherapy was associated with improved survival for pN+ patients (HR=0.324, 95%CI:0.138-0.760, p=0.010). Conclusions: For patients without pathologic lymph node metastasis, there is a survival benefit with adjuvant chemotherapy. However, for patients with pathologic lymph node metastasis, adjuvant chemoradiotherapy might achieve a significant survival benefit. Further prospective studies are needed to validate the results.